2019
DOI: 10.1530/joe-18-0370
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of apoptosis protect the ovarian reserve from cyclophosphamide

Abstract: Cancer therapy can cause off-target effects including ovarian damage, which may result in primary ovarian insufficiency in girls and premenopausal women. Loss of ovarian follicles within the ovarian reserve leads to ovarian endocrine dysfunction and impaired fertility. Cyclophosphamide (CPA), a commonly used chemotherapeutic and immunosuppressant agent, is a gonadotoxic agent that destroys ovarian cells by crosslinking DNA. To protect the ovary against CPA damage, we sought to precisely map the mechanism by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 42 publications
16
106
0
Order By: Relevance
“…Despite a dramatic increase in CASP3 positive cells in the WT mice post-PM exposure, fewer cells positively stained for CASP3 in Atm +/female mice after PM exposure. This finding in the WT mice is consistent with previous studies [21,25,43,67]. DNA damage can also activate the mitochondrial apoptosis pathway and CYCS release [68].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite a dramatic increase in CASP3 positive cells in the WT mice post-PM exposure, fewer cells positively stained for CASP3 in Atm +/female mice after PM exposure. This finding in the WT mice is consistent with previous studies [21,25,43,67]. DNA damage can also activate the mitochondrial apoptosis pathway and CYCS release [68].…”
Section: Discussionsupporting
confidence: 93%
“…Direct toxicity to the follicle or oocyte may occur [40][41][42][43] or accelerated hyperactivation of primordial follicles [44] in response to targeted death of larger growing follicles, resulting in follicular "burnout" [45][46][47]. PM induces ovarian DNA damage in the oocyte and granulosa cells [22,24,25] and our group discovered that ATM inhibition prevents PM-induced follicle depletion [31].…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes within primordial follicles exist in a relatively quiescent state, and hence may be relatively resistant to antimitotic agents [8], but the effects of alkylating agents are independent of the cell cycle. On the other hand, recent studies have shown that CY is also capable of damaging the primordial follicles in murine ovaries [7,9]. Rodents exposed to CY in pregnancy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Of them, Zbtb1 is a member of the Krüppel C2H2-type zinc-nger protein family and regulated by the PI3K/PTEN/AKT pathway, which has a critical role in regulating dormancy and initial primordial follicle activation [28]. However, exposure to Cy disturbs this balance by destroying growing follicles or activating the PI3K/PTEN/Akt pathway, causing reservoir "burnout" [29,30].…”
Section: Discussionmentioning
confidence: 99%